The Effect of Nurses' Personality Traits on Innovative Behaviors: A Cross-sectional Study - Nurcan Bilgin; Aydın Akar; Adalet Kutlu (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study was conducted to investigate the effect of nurses' personality traits on innovative behaviors. Method: The population of this descriptive and cross-sectional and relationship seeking study included 245 nurses, with a sample size of 150 nurses worked in a state hospital between June 2023 and January 2024. Data collection tools were the Information Form, Ten-Item Personality Inventory, and Individual Innovativeness Scale. The number and percentage distributions and descriptive statistics of the descriptive characteristics were calculated. The Kruskal Wallis test and Pearson correlation analysis were used in univariate analysis, and multiple regression analyses were used in multivariate analyses. Ethical approval for the study was obtained from a university's ethics committee. Results: In this study, it was found that there was a weak positive relationship between the sub-dimensions of extraversion, agreeableness, conscientiousness, emotional stability and openness to experience and the individual innovativeness scale, and significant predictors of individual innovativeness of nurses were extraversion and conscientiousness. It was found that there was a significant difference between the individual innovativeness levels of the nurses and the extraversion and conscientiousness sub-dimensions (p<0.05), and the mean scores of the innovative nurses were higher than the average scores of the skeptical nurses. Conclusion: The most important personality traits predicting nurses' individual innovativeness were extroversion and responsibility. For this reason, it is recommended that managers in healthcare institutions include personality tests in their corporate recruitment and selection processes to encourage nurses' innovation.